2019
DOI: 10.7861/fhj.2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Flipped learning: Turning medical education upside down

Abstract: ResultsStudent feedback showed a significant improvement in satisfaction with flipped learning compared to standard lectures, both in scores and free-text feedback. Results of in-course assessments did not change between the two methods of delivery. ConclusionsFlipped learning can improve student satisfaction and engagement with teaching, but our study has not demonstrated an improvement in assessment scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…This is supported by the results of a study by Lapitan et al [32], where they reported that a newly developed blended method of learning had positive impact on both teachers and students. This might be due to the ipped nature of blended learning, where the students can learn the theoretical part of lessons before coming to the classroom to do practical exercises facilitated by the teachers [33,34]. This is supported also by results from focus group discussions, where teachers reported that it would be better to mix between online learning for the theory parts of lessons (where students can do on their own pace before class) and faceto-face learning for deeper and more practical teaching in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the results of a study by Lapitan et al [32], where they reported that a newly developed blended method of learning had positive impact on both teachers and students. This might be due to the ipped nature of blended learning, where the students can learn the theoretical part of lessons before coming to the classroom to do practical exercises facilitated by the teachers [33,34]. This is supported also by results from focus group discussions, where teachers reported that it would be better to mix between online learning for the theory parts of lessons (where students can do on their own pace before class) and faceto-face learning for deeper and more practical teaching in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…The network of sensors in the house is adequately positioned and recorded all the normal activities in the house at a particular period (Al-Yahya and Panuwatwanich, 2018). Mortimer et al (2018) stated that using intelligence and information that the system has learned about the residents, it makes decisions about whether to lock doors and windows; turn on or off the heater, air conditioner, lights or entertainment systems; or activate the security system (Mortimer et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainable smart housing development encompasses a housing design that reduces a house's effect on the environment and community by complying with the principle of sustainability (Beneke et al , 2013). Smart housing captures both the computerization and the transformation of architectural, structural and services design features of the building products (Mortimer et al , 2018). This includes domestic appliances and electronic devices that are selected to optimize energy, water, and material efficiencies as well as to enhance resource management and ease of operation (Mortimer et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 An example of a relatively easy change to refresh any stale session or programme is described in a paper on 'flipped' learning -outlining benefits and some tips for troubleshooting. 6 The senior leadership of the (soon-to-be regulated) Faculty of Physician Associates and co-contributers discuss learning in the modern team from the perspective of physician associates (PAs) and their shared experiences -a topic that has been covered in depth with a number of real-life practical examples in the Royal College of Physicians' (RCP's) report Never too busy to learn . 7,8 In addition, our personal learning is strengthened from not always succeeding and may be even more significant in our development as described in 'Not winning is good for you'.…”
Section: Learning To Speak Up and To Learn Differentlymentioning
confidence: 99%